Driving license renewal (2014)
This essay originally intended to put into context the reader on the management of the Ministry of Transport, functions, organization, forming, framing the regulations and otherwise illustrate the legislation governing the transport Colombia, its requirements, requirements, limitations , among others. Additionally a point of view on the subject is raised, pointing out the process of issuing